2010
DOI: 10.1016/j.anireprosci.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The first ovulation of the breeding season in the mare: The effect of progesterone priming on pregnancy rate and breeding management (hCG response rate and number of services per cycle and mare)

Abstract: The mare is a seasonally polyestrus breeder. In early spring, the mare enters a "transition period" between the anovulatory season and the first ovulation of the year. This period is characterized by irregular estrus cycles and high incidence of regressing dominant follicles. There is a belief that pregnancy rates resulting from the first ovulation of the season is lower than in subsequent ovulations, however this has never been studied critically. Progestagens are often used as an aid to manage the transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
0
10
2
Order By: Relevance
“…However, this value was similar to that observed in non‐treated mares during the first ovulation of the breeding season (46.7%). This percentage was slightly lower than described by Hanlon and Firth (), but strongly lower than that reported by Cuervo‐Arango and Clark (). Both studies conclude that pregnancy rate was not affected by progesterone priming treatment, in agreement with data here obtained.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…However, this value was similar to that observed in non‐treated mares during the first ovulation of the breeding season (46.7%). This percentage was slightly lower than described by Hanlon and Firth (), but strongly lower than that reported by Cuervo‐Arango and Clark (). Both studies conclude that pregnancy rate was not affected by progesterone priming treatment, in agreement with data here obtained.…”
Section: Discussioncontrasting
confidence: 67%
“…As previously reported by Cuervo‐Arango and Clark (), treatment of transitional mares with intravaginal progesterone‐releasing devices has significant advantages in improving the breeding management during a difficult time of the year for both the veterinarian and the stud manager. In group T2, the progesterone levels drop below 1 ng/ml on day 11, showing that the progesterone release is much reduced at this time, and suggesting that shorter treatments could exert a similar effect.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus both the means and ranges of growth rates, and pre-ovulatory diameters were almost identical for both groups. Previous studies found non-significant differences in pregnancy rate between ovulations from first and subsequent cycles in thoroughbred mares, 65.2% v. 76.0% [8] and 67.2% v.73.7% (Newcombe and Cuervo-Arango: unpublished). In the latter study, the multiple pregnancy rate was 50% higher at second cycles (23.8% v. 15.7%).…”
Section: Discussionmentioning
confidence: 98%
“…The use of an intravaginal progesterone‐releasing devices (PRID/CIDR) have been investigated for hastening the first ovulation, but with mixed results. CIDRs impregnated with progesterone were found ineffective in improving pregnancy rates on the first cycle (Cuervo‐Arango and Clark 2010), while Newcombe reported 89% of anoestrus mares to ovulate within 10 days following the removal of a progesterone‐releasing intravaginal devices (PRIDs) (Newcombe 2002). It should be noted that mild‐to‐moderate vaginitis is reported in a subset of mares following implantation of the progesterone‐releasing devices, and the devices are not approved for equine use in most countries (Crabtree et al 2018).…”
Section: Effects Of Progestins On the Reproductive Tractmentioning
confidence: 99%